Profil Kondisi Masyarakat Korban Longsor (Studi di Desa Muaro Air Kecamatan Bayang Utara Kabupaten Pesisir Selatan). - Sari, Dewi Ratna; Hasan, Marwisni; Gusneli, Gusneli (Bimbingan dan Konseling, 2013)
This problem is motivated by the citizen of landslides victims.With the landslide many people feel sad, trauma, stress, disappointment and even despair, as well aswith the disaster also make sphysical condition they were interrupted. The purposeof this study is to see how the psychological state and physical condition of the victims of landslide. In this thesis, the type of research is a type of field research by using qualitative research, with descriptive type shaped words written or spoken of the object being observed. Through Snowball sampling techniques, which are sampling a small amount at first, then growing like a snowball. Based on the results of a study of the landslide victims in the village of Muaro Air, sub-district of Bayang Utara, Pesisir Selatan regency, it can be concluded that the psychological condition of avalanche victims are generally disturbed, they still feel scared and saddened by the landslide, felt hopeless, and felt no longer afford to buy the goods that have been lost. So also with their physical condition, many of those who disturbed his physical condition, insomnia, decreased appetite, and their durability is weak, resulting in disease attacking easily.